Modulation of gut microbiome by probiotics in obesity and related metabolic abnormalities / Mohd Shafiq Aazmi - Aazmi, Mohd Shafiq (Institute of Graduate Studies, UiTM, 2017)
Accumulating evidence suggests that the aberrant taxonomic composition of gut microbiota is one of the etiological factor in the development of obesity. With the inherent plasticity of gut microbiota structure, it provides a new avenue for the application of biotherapeutics to modulate the shifted structure of microbiota in obesity. Lately, much attention has been focused on probiotic as a biotherapeutics candidate for obesity. In contrast, knowledge on the modulating effects of probiotic on the obese gut microbiota structure is still limited and should be evaluated. The present study aims to elucidate the inherent plasticity of gut microbiota and the dynamic response of the host metabolism during the induction of high-fat-diet-induced obesity and upon the amelioration of obesity by probiotics in obese rat models. Two probiotic candidates; (i) single strain Lactobacillus casei strain Shirota (LAB13) and (ii) probiotic cocktail LACTO-5™ (L. rhamnosus, L. acidophilus, B. subtilis, B. longum and S. thermophilus) were supplemented to the obese rats at doses of 1 ×109 CFU per/day/rat for 12 weeks. The probiotic treatment started after the induction of obesity using high fat diet (HFD, 60% fat). The heterogeneity of gut microbiota structure and its functional complement genes were profiled from the faecal samples of rats from each intervention group (n=3/group) using shotgun metagenomics sequencing. Phenotypically, the weight gain, energy intake, subcutaneous fat, total fat weights, total cholesterol, leptin, ratio of TC to HDL-c and leptin to adiponectin in obese rats were significantly reduced by the supplementation of both probiotics. These confirmed the anti-obesity, hypocholesterolemic and hypoleptinemia effects of both probiotics…